Effect of Non-Newtonian Convective Unsteady MHD Flow of Fluids on an Inclined Plate in a Porous Medium with Boundary Slip and Heat Source - Monika Kalra, Rajni (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this research paper I have calculated and computed some of the important aspects of Impact of Convective, Unsteady MHD Flow of Fluids having Non-Newtonian Character, on Inclined Plate in a Medium of Porous Nature, with Boundary Slip, Including Heat Source. The theme of this research paper is to investigate non- Newtonian character on porous material plate in inclined position with the slip condition. The motive of investigation of this research paper is to find out certain rare results for the fluid dynamics. The problem has been solved analytically using mat lab by solving various equations culminating through process. Velocity, temperature, skin friction values/ profiles have been obtained in the wake of non-dimensional parameters such as magnetic, permeability including heat source along with Prandtl and Grashof number The present problem deals with non-Newtonian unsteady, electrically conducting fluid MHD, convective flow, on Semi-infinite, inclined plate of porous material, held in oscillating position in porous medium, with suction, over which the fluid is allowed to flow while a transverse magnetic field acted on it and velocity slip condition applied on it at the boundary. It will help the researchers for future research and experiments with different non-Newtonian fluids to find impact of slip flow using plate in inclined position.